2013
DOI: 10.1680/geng.12.00103
|View full text |Cite
|
Sign up to set email alerts
|

Ground heave induced by installing stone columns in clay soils

Abstract: Measurements of ground heave induced by installing stone columns in soft clay are presented in this paper. These measurements are likely to provide guidance to practitioners concerned about the possible impact of column construction on adjacent structures and services. Heaved volume, variation in heave with radius and the radial extent of heave were found to follow experience of driven piles. Simplified finite-element analyses have also been performed which indicate that the thin stiff crust typical of soft cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Experimental and numerical studies showed that the lateral expansion towards the surrounding soil by ramming aggregates in a pre-bored hole could increase the horizontal stresses in the soil, increase the load capacity of the column and reduce the settlement of the column . McCabe et al (2013) reported that the installation of displacement stone columns could induce ground heave up to a distance of 20 times the radius of the column. Shen et al (2008) showed that the strength of the surrounding sensitive clay by deep mixing first decreased and then mostly regained or even exceeded its original strength after column installation.…”
Section: Installationmentioning
confidence: 99%
“…Experimental and numerical studies showed that the lateral expansion towards the surrounding soil by ramming aggregates in a pre-bored hole could increase the horizontal stresses in the soil, increase the load capacity of the column and reduce the settlement of the column . McCabe et al (2013) reported that the installation of displacement stone columns could induce ground heave up to a distance of 20 times the radius of the column. Shen et al (2008) showed that the strength of the surrounding sensitive clay by deep mixing first decreased and then mostly regained or even exceeded its original strength after column installation.…”
Section: Installationmentioning
confidence: 99%
“…The concept of encasing granular columns with geosynthetics to increase their capacity has been acknowledged by numerous researchers (Raithel and Kempfert, 2000;Kempfert et al, 2002;Raithel et al, 2002;Alexiew et al, 2005;Brokemper et al, 2006;Murugesan and Rajagopal, 2006, 2007, 2010Lee et al, 2007;Yoo et al, 2007;Gniel and Bouazza, 2009;Hong, 2009, 2014;Yoo and Kim, 2009;Yoo, 2010;Yoo and Lee, 2012;Zhang et al, 2012;Almeida et al, 2013;Dash and Bora, 2013;Elsawy, 2013;Maheshwari and Chauhan, 2013;McCabe et al, 2013;Shahu, and Reddy, 2014;Ali et al, 2014). In addition to its ground improvement effect in terms of load carrying capacity, Tang et al (2013) has demonstrated the effectiveness of geosynthetic encased stone columns for ground improvement of liquefaction mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…The paper shows that although lateral bulging up to 25% occurred, there was still significant potential for improvements to surface foundations. This is a slightly different approach and focus to the paper in GE in December 2013, which considered the finite-element modelling of heave induced by stone column installation in clays (McCabe et al, 2013).…”
mentioning
confidence: 99%